2018
DOI: 10.1038/s41598-018-35776-8
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory cleft proteome does not reflect olfactory performance in patients with idiopathic and postinfectious olfactory disorder: A pilot study

Abstract: Technical advances including liquid chromatography–tandem mass spectrometry and its data analysis enable detailed proteomic analysis of the nasal mucus. Alterations of the nasal mucus proteome may provoke substantial changes of the nasal physiology and have already been associated with rhinologic diseases such as allergic rhinitis. This study was conducted as a pilot study to map the olfactory cleft proteome using current techniques for proteomic analysis. Furthermore, we aimed to investigate proteomic changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 38 publications
4
8
0
Order By: Relevance
“…It is unlikely that UGT could be present in the mucus because its activity has been shown to be dependent to the surrounding phospholipids in the membrane [30][31][32]. Accordingly, proteomic studies did not evidence UGT protein in the mucus in rat or human [4,[33][34][35], while, as confirmed by our results, UGT2A1 has been detected in olfactory cilia proteome [36,37]. One should note that cross-reactivity of the antibodies with the UGT2A2 variant cannot be ruled out.…”
Section: Discussionsupporting
confidence: 64%
“…It is unlikely that UGT could be present in the mucus because its activity has been shown to be dependent to the surrounding phospholipids in the membrane [30][31][32]. Accordingly, proteomic studies did not evidence UGT protein in the mucus in rat or human [4,[33][34][35], while, as confirmed by our results, UGT2A1 has been detected in olfactory cilia proteome [36,37]. One should note that cross-reactivity of the antibodies with the UGT2A2 variant cannot be ruled out.…”
Section: Discussionsupporting
confidence: 64%
“…Comparison of results to other published studies showed that 69 of 84 proteins (82%) detected by Débat et al 12 were identified in the present study. Similarly, 1075 of 1117 proteins (96%) detected by Wolf et al 13 were detected in the present study. The overall number of mucus proteins in the current study (N = 2514) was similar to that reported in the OC mucus of non-CRS aging subjects (N = 2586).…”
Section: Statistical and Proteome Bioinformatics Data Analysissupporting
confidence: 85%
“…12 Using current shotgun techniques, 2 additional studies have been reported within the last 2 years, both identifying well over 1000 unique proteins. 13,14 However, neither of these studies included patients with CRS. It thus remains unknown whether the proteomic profile of patients with CRS differs from controls without CRS, particularly with regard to OBPs or metabolizing enzymes, nor is it known whether changes are associated with olfactory function.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This technique is well tolerated and has the advantage of minimal stimulation and/or trauma to the mucosa. Moreover, certain areas of the nose can be directly suctioned under endoscopic control, for example the middle meatus or the olfactory cleft (235) .…”
Section: Nasal Suctioningmentioning
confidence: 99%